HUBUNGAN ANTARA KESEGARAN JASMANI, DISIPLIN DAN PERCAYA DIRI TARUNA DENGAN PRESTASI AKADEMIK TARUNA SEKOLAH TINGGI TRANSPORTASI DARAT BEKASI JAWA BARAT - Santoso Santoso; Evi Susianti (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2017)
The objective of this research is to study between physical fitness, discipline, and self-confidence with academic achievement. The research was conducted at Land Transport Academy in Bekasi West Java, with n=118 cadets were selected randomly. The data was analyzed using simple correlation, multiple correlations, simple regression and multiple regressions. The research concludes that there is positive correlation between: (1) Physical Fitness and academic achievement, (2) discipline and academic achievement, (3) Self Confidence and academic achievement, and (4) physical Fitness, discipline, and self-confidence with academic achievement. Therefore, Academic achievement can be improved by improving physical fitness, discipline, and Self Confidence.